Social Media and Role of Health Care Professionals: Past, Present and Future Direction (East West Medical College Journal, 2024)
Health care professionals can use social media for variety of purposes. Social media has huge impact in terms of patient education, awareness buildup and patient management strategies. Global impact of social media has been undoubtedly appreciable in terms of different awareness programs. At the same time, for personal branding, social media is contributing more and more than ever. However, potential risks related to unreliable information, violation of medical ethics including patient’s privacy rights should always be considered for safe use of social media and for personal safety against nations copyright act.EWMCJ Vol. 12, No. 1&2, January-July 2024: 1-3